2017
DOI: 10.5505/tjtes.2017.56884
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography use in minor head injury: attitudes and practices of emergency physicians, neurosurgeons and radiologists in Turkey

Abstract: BACKGROUND: We aimed to determine the attitudes and practices of emergency physicians (EPs), neurosurgeons, and radiologists in Turkey regarding computed tomography (CT) use for adults with minor head injury (MHI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…This rate was similar (75.5%) in our study. The rate of emergency physicians who decided upon the expectations of patients and/or their relatives about taking CCT was 72.6% in the same study (18). The rate of the participants who thought that the family's request to take a CT scan affected their decision was found to be 60.1% in our study.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…This rate was similar (75.5%) in our study. The rate of emergency physicians who decided upon the expectations of patients and/or their relatives about taking CCT was 72.6% in the same study (18). The rate of the participants who thought that the family's request to take a CT scan affected their decision was found to be 60.1% in our study.…”
Section: Discussionsupporting
confidence: 63%
“…The most common factors that physicians participated in our survey complained were the fear of malpractice and the request of the families to take CCT. In the study, Özan and Ataç (18) reported that malpractice anxiety was seen in 73.6% of the emergency department physicians as the reason for not applying CDMRs in minor head injury in adults. This rate was similar (75.5%) in our study.…”
Section: Discussionmentioning
confidence: 97%